Clinical and bacteriological profile of neonatal sepsis with emerging resistance patterns - Rajana, Rohitashwa; Bagri, Dhan Raj; Sharma, J. N.; Agrawal, Vijay (International Journal of Contemporary Pediatrics, 2018)
Background: The present study was designed to evaluate the clinical spectrum, bacteriological profile, antibiotic sensitivity pattern and mortality due to neonatal septicemia in neonates admitted in neonatal units attached to the SMS Medical College, Jaipur. Methods: In born and out born babies of postnatal age up to 28 days who were bacteriological proven cases of septicemia were subjected to history, clinical examination and laboratory evaluation and data were analyzed statistically. Results: Out of 150 cases 67.33% neonates were preterm and 77.33% were low birth weight neonates. Gram negative organisms were most common cause of septicemia (66.6%), Both the Gram negative and Gram positive organisms were sensitive to piperacillin-tazobactam, linezolid, fosfomycin, teicoplanin, polymyxin B, colistin, ofloxacin. Both the Gram negative and Gram positive organisms were resistant against cephalosporins, ampicillin, Amoxyclav, cotrimoxazole. Gram negative isolates were most sensitive to Polymyxin B (70%) and had the highest resistance to cefepime (36%). Gram-positive organisms were most sensitive to vancomycin (84%) and linezolid (82%). Highest resistance was noted from Amoxyclav (52%). Conclusions: Preterm (<37 week) and low birth weight (<2500gm) neonates are considered as major susceptible causes of neonatal sepsis. Proper hygiene and hand washing, early detection of sepsis and judicial use of antibiotics to prevent multidrug resistance is needful in our setup.